Exosome-Mediated Transfer of X-Motif-Tagged Anti-MiR-33a-5p Antagomirs to the Medial Cells of Transduced Rabbit Carotid Arteries - Goren Saenz-Pipaon; Bradley K. Wacker; Lianxiang Bi; Alexis Stamatikos; David A. Dichek (Biology)
Atherosclerosis is caused by the accumulation of cholesterol within intimal smooth muscle cells (SMCs) and macrophages. However, the transporter ATP-binding cassette subfamily A, member 1 (ABCA1), can remove cholesterol from these intimal, cells reducing atherosclerosis. Antagomir-mediated inhibition of miR-33a-5p, a microRNA that represses ABCA1 translation, promotes ABCA1-dependent cholesterol efflux and may impede atherosclerosis development. In our previous work, transducing cultured endothelial cells (ECs) with a helper-dependent adenoviral vector (HDAd) that expresses X-motif-tagged anti-miR-33a-5p enhanced antagomir packaging into EC-derived exosomes, which delivered the antagomir to cultured SMCs and macrophages. In this present study, we tested whether in vivo transduction of rabbit carotid artery endothelium can deliver an X-motif-tagged anti-miR-33a-5p to subendothelial cells. Rabbit carotid endothelial cells were transduced in vivo with an HDAd expressing anti-miR-33a-5p either with or without the X-motif (n = 11 arteries per vector). Contralateral carotids received HDAd that express scrambled oligonucleotides. Three days after transduction, the antagomir—without the X-motif—was detected in the intima but not in the media of transduced carotids (p = 0.062). The X-motif antagomir was detected in 82% of the intimal extracts (9 out of 11 carotids) and 27% of medial samples (3 out of 11 carotids, p = 0.031). However, the X-motif did not significantly enhance antagomir delivery to the media (p = 0.214 vs. non-X-motif antagomir). Expression of the antagomirs—with and without the X-motif—was sub-stoichiometric in ECs and SMCs. No antagomir-related changes in miR-33a-5p or ABCA1 expressions were detected. Despite its potential as a therapeutic strategy, our exosome-targeted gene transfer system requires further improvements to enhance antagomir expression and delivery to the subendothelial cells.